Add-on premiums increase price transparency: More policy holders switch health plans - Peter Eibich; Hendrik Schmitz; Nicolas R. Ziebarth (DIW Economic Bulletin, 2012)
The German health care reform implemented in 2009 led to a considerable increase in price transparency within the statutory health insurance (SHI) (Gesetzliche Krankenversicherung, GKV) system and also made it more consumer-friendly which, in turn, has encouraged policy holders to react to price hikes by switching to a different health insurance fund (sickness fund). In 2009, the government established a central health care fund (Gesundheitsfond) which standardized contribution rates. Price differences between the sickness funds are now listed separately on the policy holder's bill as add-on or reimbursed premiums. It is above all these add-on premiums that gave policy holders a clear price signal. According to SOEP representative survey data, in 2010 this resulted in one in ten individuals affected by add-on premiums switching health plans. Aggregated sickness fund level data show that the add-on premiums introduced by the DAK and KKH-Allianz resulted in a 7.5 percent average annual loss of members. However, at the beginning of 2011, a generous increase in the uniform contribution rate for all sickness funds and the extravagant filling of the health care fund with the additional reserves means that in 2012, it is likely that no sickness fund will have to charge add-on premiums thus thwarting any price transparency previously achieved by the add-on premiums. As of 2013 the situation could change again as a result of increasing health care spending and a downturn in the economy. However, the government should not count on this happening, and instead should introduce new incentives to strengthen price competition, for example by capping the health care fund's payments to the sickness.
Keywords: H51; I11; I18; 330; health insurance; price framing; health plan switching; SOEP